Soluble angiotensin-converting enzyme 2 association with lipid metabolism - Nagatomo, Izumi; Nakanishi, Kaori; Yamamoto, Ryohei; Ide, Seiko; Ishibashi, Chisaki; Moriyama, Toshiki; Yamauchi-Takihara, Keiko (Frontiers in Medicine, 2022)
Increased expression of angiotensin-converting enzyme-2 (ACE2) is one of the likely explanations for disease severity in patients with coronavirus disease 2019 (COVID-19). In this study, we aimed to test whether soluble ACE2 (sACE2) levels are correlated to known risk factors of severe COVID-19 including biochemical parameters, body mass index and smoking habits. We cross-sectionally evaluated serum sACE2 levels in obese or tobacco-smoking populations and compared them to those in non-obese and non-smoking healthy participants. Additionally, fibroblast growth factor-21 (FGF21) was investigated as a candidate regulator of sACE2. A total of 220 male participants aged 30–59 years undergoing an annual health checkup were enrolled in this study: 59 obese, 80 smokers, and 81 healthy. Serum sACE2 levels were significantly higher in obese participants but not in tobacco-smoking participants when compared to healthy participants. sACE2 levels were significantly correlated with total cholesterol and triglycerides but not with body mass index. Furthermore, no regulatory relationship was found between FGF21 and sACE2. Lipid metabolism disorders accompanied by upregulation of serum sACE2 may be underlying mechanisms of COVID-19 aggravation and might be a novel breakthrough treatment target.